Analisis Kinerja Keuangan PT.BISI Internasional Tbk: Perspektif Manajemen dan PemilikAnalisis Kinerja Keuangan PT.BISI Internasional Tbk: Perspektif Manajemen dan Pemilik - Nur Azizah; Yovanna Nabila Azzahra (BADAN PENERBIT STIEPARI PRESS, 2024)
When the Covid-19 pandemic occurred, many companies were in a difficult situation to earn income and make a profit, of course this problem affected PT. BISI Internasional Tbk. After the post-Covid period of 2022, the company experienced an increase. This research aims to analyze the financial performance of the company PT. BISI International Tbk. which uses secondary financial report data and has been published by PT. BISI International Tbk. from the 2020-2022 period. Data can be accessed via the company website https://www.bisi.co.id. Then from this data the author analyzes using the ratio formula from the perspective of management and owner. The method of this research uses a descriptive method using data from the research object. The results from a management perspective show a positive value in the profit percentage for the 2020-2022 period and show that financial performance is good, this is shown in a decrease in the number of aging receivables and a decrease in operating expenses. Despite having constraints in resource management, the company experienced an increase in the working capital ratio from the previous year. Based on the perspective of company ownership, it can produce net profits and an increase in profits per share which results in high profits, so that the company is considered healthy.